Transport studies in quasi one-dimensional III-V wires, tubes, and fin structures - Xing, Dai (2014)
The semiconductor industry is one of the fastest-growing market segments in the world. To overcome the bottleneck encountered in downscaling Si-based technology, introduction of alternative materials and low-dimensional systems are highly demanded. III-V compound semiconductors promise a great potential for (opto)electronics, owing to intrinsic properties such as high electron mobility and direct bandgap, as well as the ability to build complex functional heterostructures for bandgap engineering. Both bottom-up synthesis and top-down fabrication allow the development of one-dimensional systems such as single nanowires, nanowire junctions, nanowire heterostructures and Fin structures, which offer new degrees of freedom for the design of transport properties. We discuss fundamental issues related to material synthesis, surface state control, carrier transport, and heterogeneous integration of quasi one-dimensional III-V compounds in unconventional geometries, toward their application in highly integrated electronic and light detecting devices.